Temporalidades contemporâneas ressignificadas: lógicas de consumo e representações de passado e futuros no cenário ficcional de Tormenta RPG - Tancini, Pedro Ernesto Gandine (2018)
This master thesis turns on time representations and memory movements in the contemporary context of consumption. We pick the setting Tormenta RPG as the object of research. Role-playing game, RPG, is a game format in which players experience narratives in an improvised and collaborative way. Tormenta RPG, in turn, is an editorial brand that, through descriptive books, builds a fictional environment for this game, promoting a universe inspired in medieval fantasy but with reference to different non-medieval contexts. We investigate how the text of Tormenta RPG, by operating time representations allied to the appropriation of medieval fantasy and others historical imaginaries, resignifies the temporalities relating to the culture of consumption and culture of memory contexts. The methodology involves, first, bibliographical research around the concept of time, memory and consumption, with reference to authors such as N. Elias, G. Szamosi, R. Koselleck, concerning the time in its structural quality and in the modernity arrival, Z. Bauman, A. Huyssen, D. Harvey, F. Hartog, concerning the contemporary temporalities, culture of memory and culture of consumption. As of this theoretical core, we develop analysis of the “timeline” text introduced by the book “Tormenta RPG”, based on categories created from the cultural semiotics studies of I. Lotman. We expect to explore the qualities that the time representations and the memory movements, articulated to the consumption logics, imprint in the composition of our actual temporalities, in how we bring our pasts do the present and how we imagine our futures.